PENINGKATAN KUALITAS BELAJAR MATEMATIKA SISWA SMA PADAMU NEGERI MELALUI QUIPPER VIDEO - Ropinus Sidabutar (Universitas Negeri Medan, 2023)
The purpose of this research is to create a mathematics learning technique to make it more interesting and also fun by carrying out online tutoring based on Quipper Video. This study uses qualitative methods with descriptive analysis. The research was conducted at Padamu Negeri Medan High School which carried out online tutoring. The results of this study are, (1) There is an increase in the quality of students' mathematics learning in the aspects of results, motivation, and aspects of the lesson plan. (2) The